(untitled) (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Resection of dorsal hump often leaves a widened, flat and open roof deformity, causing weakness at keystone area and diminishing the nasal valve angle. Incorporating spreader grafts or spreader flaps along the dorsum helps prevent these issues, providing both structural reinforcement and a restoration of dorsal aesthetic lines. The objective of this study was to identify the value of spreader graft and spreader flap in dorsal reconstruction following hump reduction in primary open rhinoplasty. Methods: Prospective cross-sectional study conducted in the department of ENT-HNS of Kathmandu Medical College from April 2023 to March 2025. ROE questionnaire was used for aesthetic evaluation while NOSE scale was used for evaluation of functional outcomes. Descriptive statistics was used for comparative analysis of preoperative and postoperative ROE and NOSE scores. Results: Preoperative ROE scores averaged (6.85 ± 0.69), rising markedly to (17.01 ± 1.14) at 3 months and (18.92 ± 2.08) at 6 months, demonstrating a statistically significant improvement (P < 0.001). In both the groups preoperative NOSE scale value was (42.29 ± 17.20), which showed marked improvement when re-evaluated at 3 months (29.55 ± 2.84), and 6 months (26.31 ± 2.19) postoperatively. Conclusion: In rhinoplasty, effective management to restore the nasal valve angle after dorsal hump reduction includes the use of spreader grafts or auto-spreader flaps. These techniques help to preserve or reconstruct the dorsal aesthetic lines while simultaneously supporting improved nasal patency and airflow for optimal functional results.